2018
DOI: 10.1038/s41598-018-30747-5
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap of strain in doped anatase TiO2

Abstract: Anatase titanium oxide is important for its high chemical stability and photocatalytic properties, however, the latter are plagued by its large band gap that limits its activity to only a small percentage of the solar spectrum. In that respect, straining the material can reduce its band gap increasing the photocatalytic activity of titanium oxide. We apply density functional theory with the introduction of the Hubbard + U model, to investigate the impact of stress on the electronic structure of anatase in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
(38 reference statements)
4
16
0
Order By: Relevance
“…The energy states at 2.4 eV are created from the hybridization of Cr-3d with Ti-3d orbitals. The results are in good agreement with other theoretical works [51]. In Figure 3b, the CrTi:TiO2 case is examined.…”
Section: Structural and Electronic Propertiessupporting
confidence: 90%
“…The energy states at 2.4 eV are created from the hybridization of Cr-3d with Ti-3d orbitals. The results are in good agreement with other theoretical works [51]. In Figure 3b, the CrTi:TiO2 case is examined.…”
Section: Structural and Electronic Propertiessupporting
confidence: 90%
“…Our calculations were performed with DFT + U model with the Hubbard-U parameter equal to 8.2 eV 33,34 . We calculated the band gap at 3.14 eV, in agreement with previous theoretical studies 33,34,44 , which show a band gap narrowing from 3 to 3.16 eV and close to the experimental value of 3.2 eV.
Figure 3( a ) DOS of the undoped bulk anatase TiO 2 , ( b ) DOS of interstitially F - doped TiO 2 ( c ) DOS of F:TiO 2 with F substituting an Oxygen site and displacing it to an interstitial site. ( d ) DOS of the F:TiO 2 when F is a substitution to O, ( e ) The Density of States graph of the Cl-Doped TiO 2 with Cl as an interstitial, ( f ) The Density of States graph of the Cl:TiO 2 when Cl is a substitution to O.
…”
Section: Resultsmentioning
confidence: 99%
“…A common way to reduce the band gap of TiO 2 is through doping with appropriate elements which has also significant impact on its electronic structure. A vast variety of literature reports previously demonstrated that by doping TiO 2 with nitrogen (N), halogens such as fluorine (F) and chlorine (Cl), or several transition metal ions such as zinc (Zn) or nickel (Ni), significant changes in its electronic structure are observed 2834 . Particularly, the formation of mid gap states resulting in a band gap reduction was evident.…”
Section: Introductionmentioning
confidence: 99%
“…We present quantitative and physically intuitive arguments that explain the origins of such irregular η-driven effects on E g in terms of dielectric susceptibility and metal-oxygen bond length changes. It is worth noting that recent experimental and theoretical works have already proposed epitaxial strain as a means for tuning E g in some oxide materials such as TiO 2 [17,18], ZnO [16], SnO 2 [19], and CdO [20]. However, a clear and general understanding of how biaxial strain affects the photocatalytic performance of binary oxides is still missing.…”
Section: Introductionmentioning
confidence: 99%